The Pattern of Distribution Salinity and Temperature at The Flood Tide and Ebb Tide in The Strait Bengkalis Riau Province - Rizki, Fariza; Ghalib, Musrifin; Yoswaty, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in April 2016 at the Strait of Bengkalis, Riau Province. The aim of research is to determine the pattern salinity and temperature distribution at ebb tide and flood tide. Research used survey method. Tide data obtained were presented in the form of chat the map and discussed descriptively. Based on the research it showed that average salinity at flood tide 23.56‰ and ebb tide 22.90 ‰. The average of salinity at ebb tide was lower than flood tide. In contrast to the temperature, the temperature measurement at flood tide lower than ebb tide and the average value at flood tide 31,18ºC and ebb tide was 31,53ºC. The results showed that distribution of salinity and temperature during flood tide and ebb tide is fluctuated. The pattern of distribution of salinity, temperature and other environmental parameters (pH, transparency, current velocity and depth) were different betwen the flood tide and ebb tide.Keywords: Salinity, Temperature, Distribution Pattern, Bengkalis Strait